Purification and characterization of Streptococcus pyogenes superantigen (Spe-C) - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
From 144 specimens of tonsillitis which were collected from patient, (children of 3 -12 year olds) there were 70 isolates beta hemolytic and 28 isolates were identified as S. pyogenes. Sensitivity of S. pyogenes isolates to antibiotics was tested, all isolates were sensitive to amoxicillin and cephaloxia while higher resistant were to erythromycin. One isolate whiche was 100 A had a stable characteristics and produce pyrogenic toxin was chosen for study and it was purified and characterized from the cell free supernatant of S. pyrogenes strain.